MENAKAR EFEKTIVITAS PENYELESAIAN KREDIT MACET MELALUI GUGATAN SEDERHANA (Studi Kasus PT. Bank Perekonomian Rakyat Bhumikarya Pala Sleman) - Vania Valensia Firdaus; Itok Dwi Kurniawan (Verstek, 2025)
This  study  aims  to  examine  the  effectiveness  of  resolving non-performing loans through the simplified lawsuit mechanism at PT BPR Bhumikarya Pala Sleman and to analyze the legal consequences arising  from  such legal action. Non-performing loans are a serious issue in the banking sector that can disrupt  the  bank’s  operational  stability,  thus  requiring  a  fast,  simple,  and  efficient  resolution.  One alternative legal remedy is the simplified lawsuit, as regulated under Supreme Court Regulation (PERMA) No.  2 of 2015 in conjunction with PERMA No. 4 of 2019. This research employs an empirical approach, using data collection techniques through interviews and document analysis. Primary data were obtained through interviews with bank representatives, while secondary data were collected from legislation, legal literature,  and  relevant  documents  related  to  the  settlement  of  non-performing  loans.  The  findings indicate  that  simplified  lawsuits  are  effective  for  uncomplicated  cases  with  claims  not  exceeding  five hundred  million  rupiah.  This  mechanism  is  not  only  time-  and  cost-efficient  but  also  provides  legal certainty for both parties. The legal consequence is a final and binding court decision that can be directly executed, thereby offering legal protection to the creditor and encouraging the debtor’s compliance with their obligations.